PENDAMPINGAN LEGALITAS USAHA DAN AKSES PERMODALAN UNTUK PELAKU UMKM DI KECAMATAN AMANUBAN BARAT KABUPATEN TIMOR TENGAH SELATAN - Sayd, Anastasia; Sayd, Anastasia Imelda (Jurnal Pengabdian dan Pemberdayaan Banyuwangi (Jurnal Abdiwangi), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the local economy, including in Amanuban Barat District. However, the development of MSMEs in this area still faces various challenges, particularly concerning business legality and access to capital. Limited understanding of the importance of business legality, lack of information, minimal mentoring, and low financial literacy are the main factors hindering business growth. This community service program aims to enhance MSME actors’ understanding and awareness of the importance of business legality, expand access to formal financing, and improve financial literacy. The activities were carried out in the form of training consisting of three main stages: preparation, implementation, and evaluation. The results indicate an increase in participants’ understanding of business legality and capital access, the application of basic financial management practices, and the establishment of networks among MSME actors. This program provides a tangible contribution to strengthening the capacity of MSMEs to grow legally, maintain proper administrative practices, and gain access to formal financing sources.